Analysing the Effectiveness of an Online Campaign’s Messages - Siti Khadijah; Nada Muthiah Shabirah (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
Depressions among women, especially young women can happen due to the lack of support systems around them. Thus, it is important to create a support system where women can thrive from the support given to them. In this regard, Rahasia Gadis, an online community developed aims to provide a support system for women, especially young ones. This research analyzed the effectiveness of messages given in the #DariGadisKeGadis, an online campaign created by Rahasia Gadis to the participants’ eagerness to create a support system for people, especially young women around them. This research used a descriptive quantitative research design. This research applied a convenience sampling technique to obtain the participants. The results of this research indicate the positive impacts of the #DariGadisKeGadis campaign’s messages to the participants' willingness to develop a support system.